Requirements for modeling airborne microbial contamination in space stations. (March 2018) - Van Houdt, Rob; Kokkonen, Eero; Lehtimäki, Matti; Pasanen, Pertti; Leys, Natalie; Kulmala, Ilpo
Abstract: Exposure to bioaerosols is one of the facets that affect indoor air quality, especially for people living in densely populated or confined habitats, and is associated to a wide range of health effects. Good indoor air quality is thus vital and a prerequisite for fully confined environments such as space habitats. Bioaerosols and microbial contamination in these confined space stations can have significant health impacts, considering the unique prevailing conditions and constraints of such habitats. Therefore, biocontamination in space stations is strictly monitored and controlled to ensure crew and mission safety. However, efficient bioaerosol control measures rely on solid understanding and knowledge on how these bioaerosols are created and dispersed, and which factors affect the survivability of the associated microorganisms. Here we review the current knowledge gained from relevant studies in this wide and multidisciplinary area of bioaerosol dispersion modeling and biological indoor air quality control, specifically taking into account the specific space conditions. Highlights: Bioaerosol dispersion modeling is reviewed, with focus on space conditions. The behavior of microorganisms in microgravity differs from that in normal gravity. The relative importance of deposition and removal mechanisms is different in space. Validated models will help to identify microbial risk areas in space habitats.